Placental weights of neonates born with symptomatic congenital syphilis - Pillay, Shakti; Horn, Alan R.; Tooke, Lloyd (Frontiers in Pediatrics, 2023)
Background Syphilis during pregnancy remains an important global health concern causing miscarriage, stillbirth, preterm birth and neonatal death. As part of the fetal infection, placental changes occur which may include a heavier placenta than expected. Methods A cohort of 50 neonates with symptomatic congenital syphilis has previously been described. This cohort was admitted to Groote Schuur neonatal unit in Cape Town South Africa from 2011 to 2013. For this study, the placental weights of the neonates were analyzed and compared to population based placental centiles. Results There was data for 37 placentae. Heavy placentae (>90th centile) occurred in 76% of placentae in the study. All 6 infants with birth weights ≥2,500 g had heavy placentae. There was no correlation between placental centile and death. Conclusion Heavy placenta are an important and frequent finding with symptomatic congenital syphilis, especially in the larger neonates.